Are Individuals With Type 2 Diabetes Metabolically Inflexible? A Systematic Review and Meta‐Analysis - Maria Hansen; Kristine Kjær Lange; Martin Bjørn Stausholm; Flemming Dela (Endocrinology, Diabetes & Metabolism)
ABSTRACT Aim Type 2 diabetes (T2D) is characterised by insulin resistance and possibly by impaired metabolic flexibility, the latter referring to the body's ability to switch between fuel sources. This review systematically examines metabolic flexibility, measured by changes in the respiratory exchange ratio (ΔRER) during hyperinsulinaemic clamps, across lean, overweight/obese, and T2D populations. Methods A comprehensive search of PubMed identified 65 studies meeting the inclusion criteria, with 35 using a ~40 mU/m2/min insulin infusion rate for accurate comparisons. These studies included 985 participants: 256 lean, 497 overweight/obese, and 232 T2D individuals. The differences in ΔRER between the three groups were meta‐analysed. Results Basal RER values did not significantly differ across groups, but insulin‐stimulated ΔRER was higher in lean individuals compared to overweight/obese and T2D groups (ΔRER values 0.10, 0.07 and 0.07, respectively; p = 0.037) indicating greater metabolic flexibility in the lean group. However, high statistical heterogeneity in the ΔRER within‐group results (I2 values: 92.3%–94.5%) suggests considerable variability among studies. A meta‐regression analysis accounting for age, sex, and BMI indicated that only BMI was significantly associated with ΔRER. Factors contributing to the remaining heterogeneity likely include differences in participant characteristics (e.g., glycaemic control) and study design. Conclusions The review highlights the need for standardised data presentation in metabolic studies. Overall, metabolic flexibility appears more influenced by overweight status than T2D per se, challenging the notion of a distinct metabolic inflexibility threshold for T2D.